Carbon nanotubes to enable autonomous and volumetric self-heating in epoxy/polycaprolactone blends. (20th October 2020) - Jiménez-Suárez, A.; Martín-González, J.; Sánchez-Romate, Xoan F.; Prolongo, S.G.
Abstract: Carbon nanotubes (CNT) were added to epoxy/polycaprolactone (PCL) blends in order to get electrically conductive blends. As it was expected, an increase of CNT content promotes a higher electrical conductivity due to the creation of more electrical pathways. Furthermore, it was observed that the enhancement is also observed with increasing PCL content, reaching values of around 0.2 S/m for 0.2 wt % CNT and 20 wt % PCL samples, due to its effect on rheological properties of the mixture, which affect positively to the CNT dispersion process, thus leading to more homogeneous and well dispersed nanocomposites, as observed by microstructural analysis. Thermal conductivity also increases with CNT content but decreases with PCL addition due to its insulating properties. A study of the voltage required to reach the above-mentioned self-healing temperature for each material has been performed by thermography monitoring. It has been observed that the samples with the highest amount of both CNT and PCL, have the best resistive heating capabilities due to a higher thermoresistive efficiency of the electrical network, reaching temperatures above 100 °C, at voltages below 150 V. Graphical abstract: Image 1